Introducing KM Strategic Alignment Road Map in Iranian Public Agencies Studied in Tehran Regional Electricity Company - Mona Jamipor; Hamid Reza Yazdani; Freshteh Sadeghi (Journal of Information Technology Management)
Effective and on time satisfaction of organizational requirements, implementation of KM projects and above all aligning KM with business strategies are the main concerns of executives which make the existence of KM strategic alignment roadmap necessary. In order to address challenges of aligning KM with critical business needs, this paper proposed a comprehensive road map of alignment with best practices and critical success factors of KM implementation. By applying survey approach, we investigated opinions of experts which were related to the KM alignment roadmap architecture and customization of roadmap factors. Then, by using evaluating research, the application of roadmap illustrated in Regional Electricity Company. Sampling method was purposeful (judgmental) which is a non-random method. Data were analyzed by descriptive and inferential statistics. The proposed roadmap had five levels with specific factors. Regional Electricity Company was in the second level of KM strategic alignment. By applying developed road map in Regional Electricity Company, current maturity of strategic aligning KM, strength and weak points of KM project were identified. Consequently, by considering the results of assessment, future strategies, focus and investment priorities of KM were extracted.